Efficacy of fermented cereal flours and decomposed kitchen waste in - Kathar, Bablusing; Sharma, O P; Jain, H K (Indian Journal of Fisheries, 2011)
The present investigation was carried out for a period of 50 days in cement cisterns to evaluate the efficacies of fermented rice (T 1), maize (T2), wheat flour (T3) as well as decomposed kitchen waste (T4 ) in the production of microbial and zooplankton population. These were added @ 10 mg 1 –1 . The effect of different treatments on the bacterial and zooplankton population was quite significant. The average total bacterial population in 7 weeks duration was found to be highest (1817 No./ml) in T 4 , followed by T 3 (1278 No./ml), T1 (1234 No./ml), and control (662 No./ml). Highest zooplankton population of 5553 No./1 was obtained from T 4 followed by T2 (4910 No./1), T3 (4357 No./1), T1 (3220 No./1) and control (2113 No./1). The results indicated highest efficacy of decomposed kitchen waste under the existing environmental conditions. The coefficient of correlation between the average total bacterial population and average total zooplankton population was found significant.